Interferensi Leksikon Bahasa Inggris Ke Bahasa Indonesia Dalam Pembelajaran Sosiolinguistik Di Prodi PBI FKIP Universitas Sebelas Maret(UNS) - RIANGSARI, AZIZA; , Prof. Dr. Abdul Ngalim, MM., M.Hum; , Prof. Dr. Markhamah, M.Hum (2017)
This research has purpose to identify the theoretical concept of interference according to the experts in sociolinguistics learning. The research strategy used a phenomenological approach. The location of this research at Sebelas Maret University (UNS). Subjects in this study was a lecturer of the course sociolinguistics at department PBI FKIP UNS. The object of research in the form of theoretical concepts interference in the form of definitions, opinions, or views of sociolinguistics experts and lecturers. This research data in the form of words, phrases, sentences, and paragraphs that contain a theoretical concept, according from sociolinguistics experts and lecturers, then the source of the data in this study was the sociolinguistics textbook and interviews. Data collection techniques in this study used interview techniques, and FGD. Mechanical validity of the data in this study used triangulation techniques and theory. Data analysis techniques in this study used interpretation analysis, content analysis and unified intralingual. The results showed that there are nine kinds of theoretical concepts interference namely, interference is difficult, interference is an obstacle, interference is language contact, interference is fault, interference is the disruption, interference is an aberration, interference is an error, interference is language destivation, and interference is a language collection.